Influence of electromagnetic waves on viscosity and electrorheology of dielectric nanofluids-scale-based approach - Adil, M. (Penerbit UTM Press, 2016)
The appearance of electric field and shear dependent viscosity change in dielectric nanofluids provide potential for prospective applications especially in enhanced oil recovery. When nanofluids are activated by an applied electric field, it behaves as a non-Newtonian fluid under electrorheological effect, where the augment of electric field intensity increases the interaction among nanoparticles. Hence the mobility of the fluid can be efficiently controlled by regulating the applied field. Electrorheological characteristics of ZnO and Al2O3 nanofluids with various nanoparticles concentration (0.1, 0.05, 0.01 wt) were measured. Results show that all the nanofluids exhibit pseudoplastic (shear thinning) behavior, while the electric field causes a visible increase in viscosity at a high shear rate. From the experimental results, it is also explained how the polarization of induced dipoles affects the electrorheology of nanofluids, by creating chains that align with the applied electric field. This paper also describes the designing and experimental aspects of the electromagnetic system, to investigate the change in viscosity of nanofluids. Â© 2016 Penerbit UTM Press. All rights reserved.